Dawn of the Restored Latvian National Armed Forces - Baltiņa, Sarmīte (Eesti Sõjaajaloo Aastaraamat / Estonian Yearbook of Military History, 2014)
The decision on the formation of the Latvian National Guard (Zemessardze) was made in August 1991. Men who were not Latvian citizens were also invited to join the Zemessardze at first, as the Citizenship Act had not yet been passed and the Supreme Council of Latvia wanted to involve loyal non-citizens in national defence. In December 1991 there were ca 10,000 men in the 34 battalions of the Zemessardze. The Compulsory Military Service Act was adopted in September 1991 and the Ministry of Defence was formed in November. The Latvian Defence Forces were formed in November 1992. The position of the Commander of the Defence Forces was established with the National Defence Act of 1994 and a single management structure was also developed to reduce unwanted competition between the Zemessardze and the Defence Forces.The Intelligence Assault Battalion was formed in spring 1992. In 1994, Latvia joined the PfP programme and men who participated in international cooperation projects (BALTBAT) were trained in the battalion. The battalion was reorganised in 1998 and became the Latvian Peace Enforcing Battalion. The Intelligence Assault Battalion established a foundation for training Latvian soldiers who take part in foreign missions